2021
DOI: 10.1093/jee/toab228
|View full text |Cite
|
Sign up to set email alerts
|

Nontarget Impacts of Herbicides on Spiders in Orchards

Abstract: Spiders are key predators in many agroecosystems, including orchards. Despite the importance of spiders in biological control, pesticide nontarget effects on this group are poorly described. This is especially true for herbicides, which spiders frequently encounter as they move between the ground cover and tree canopy. We sought to determine the nontarget effects of seven herbicides used in orchards on three species of spiders that are commonly found in Washington state (USA) orchards: Pelegrina aeneola (Curti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…From a top‐down perspective, management intensification may reduce the diversity and abundance of natural enemies, for example through the reduction of vegetation complexity, which may result in a scarcity of nectar plants, alternative hosts, overwintering sites and other shelters (Medeiros et al, 2019; Vandermeer & Perfecto, 2010) or through the direct effects of use of pesticides on natural enemies (e.g. Schmidt‐Jeffris et al, 2022). Matching this expectation, we found that the parasitism rate was lower in the plantations than in the less intensively managed systems, which supports the hypothesis that top‐down effects could explain the higher densities of insect pests in the plantations.…”
Section: Discussionmentioning
confidence: 99%
“…From a top‐down perspective, management intensification may reduce the diversity and abundance of natural enemies, for example through the reduction of vegetation complexity, which may result in a scarcity of nectar plants, alternative hosts, overwintering sites and other shelters (Medeiros et al, 2019; Vandermeer & Perfecto, 2010) or through the direct effects of use of pesticides on natural enemies (e.g. Schmidt‐Jeffris et al, 2022). Matching this expectation, we found that the parasitism rate was lower in the plantations than in the less intensively managed systems, which supports the hypothesis that top‐down effects could explain the higher densities of insect pests in the plantations.…”
Section: Discussionmentioning
confidence: 99%
“…In the parasitoid Palmistichus elaeisis Delvare and LaSalle, glufosinate treatment reduced parasitism and emergence rates [ 40 ]. In three species of spiders found in orchards, exposure to glufosinate residues did not cause any mortality [ 13 ], but direct application increased mortality in Pardosa agrestis (Westring) [ 38 ]. The impact of glufosinate on a greater variety of natural enemies needs to be examined in the lab and the field, but the current trend indicates that glufosinate use could be particularly disruptive to integrated mite management.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these studies examined reproductive effects. Interestingly, various orchard-inhabiting spiders experienced relatively highly mortality after 48 h of exposure to residues, even though they had very little susceptibility to other herbicides tested, including paraquat and glufosinate [ 13 ]. How oxyfluorfen affects natural enemy populations in orchards merits further study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations